Resolvin D1 Improves Post-Resuscitation Cardiac and Cerebral Outcomes in A Porcine Model of Cardiac Arrest. Issue 4 (October 2020) - Chen, Weiting; Wang, Hui; Wang, Zhengquan; Zhao, Changwei; Xu, Jiefeng; Chen, Qijiang
Abstract : ABSTRACT: Following global ischemia reperfusion injury triggered by cardiac arrest (CA) and resuscitation, the ensuing cardiac and cerebral damage would result in high mortality and morbidity. Recently, resolvin D1 has been proven to have a protective effect on regional cardiac and cerebral ischemia reperfusion injury. In this study, we investigated the effects of resolvin D1 on cardiac and cerebral outcomes after cardiopulmonary resuscitation (CPR) in a porcine model. Twenty-eight male domestic pigs weighing between 33 and 41 kg were randomly divided into one of the four groups: sham, CPR, low-dose resolvin D1 (LRD), and high-dose resolvin D1 (HRD). Sham animals underwent the surgical preparation only. Other animals were subjected to 8 min of untreated ventricular fibrillation and then 5 min of CPR. At 5 min after resuscitation, resolvin D1 was intravenously administered with the doses of 0.3 and 0.6 μg/kg in the LRD and HRD groups, respectively. The resuscitated animals were monitored for 6 h and observed for an additional 18 h. After resuscitation, myocardial and neurological function were significantly impaired, and their serum levels of injury biomarkers were markedly increased in the CPR, LRD, and HRD groups compared with the sham group. In addition, tissue inflammation and oxidative stress in the heart and brain were observed in the three groups. However, myocardial function was significantly improved and its injury biomarker was significantly decreased starting 3 h after resuscitation in the LRD and HRD groups compared with the CPR group. Similarly, neurological function was significantly better at 24 h post-resuscitation and its injury biomarkers were significantly lower at 6 and 24 h post-resuscitation in the LRD and HRD groups than in the CPR group. In addition, myocardial, cerebral inflammation, and oxidative stress were significantly milder in the two resolvin D1-treated groups. Especially, HRD produced significantly greater post-resuscitation cardiac and cerebral protection compared with the LRD group. In conclusion, resolvin D1 significantly improved post-resuscitation cardiac and cerebral outcomes in a porcine model of CA, in which the protective effects may be in a dose-dependent manner.